2017
DOI: 10.1039/c7ra07627d
|View full text |Cite
|
Sign up to set email alerts
|

A 2 micron passively Q-switched bulk state pulsed laser based on WS2

Abstract: We report a 2 micron passively Q-switched bulk state pulsed laser with a pulse of 430 ns based on graphene-like 2D WS2 nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Note that there is almost no Na related states appearing around the band edge, indicating that the Na atoms only contribute to constructing the structure skeleton of NaNbO 3 , but has negligible effects on the electronic structures near the Fermi level. All these obtained results agree well with the previous experimental values and theoretical results, [20,36,37] implying that the computational methods and parameters adopted here are suitable for examining NaNbO 3 .…”
Section: Pure Nanbosupporting
confidence: 90%
See 2 more Smart Citations
“…Note that there is almost no Na related states appearing around the band edge, indicating that the Na atoms only contribute to constructing the structure skeleton of NaNbO 3 , but has negligible effects on the electronic structures near the Fermi level. All these obtained results agree well with the previous experimental values and theoretical results, [20,36,37] implying that the computational methods and parameters adopted here are suitable for examining NaNbO 3 .…”
Section: Pure Nanbosupporting
confidence: 90%
“…E 0 is and E VBM of NaNbO 3 are calculated to be −0.68 and 2.62 eV, respectively, which agrees well with the previous theoretical results. [36,37] Besides, the valence band maximum (VBM) and conduction band minimum (CBM) positions for doped systems can be obtained and aligned with the pure one by referencing to the 3s core levels of the Nb atom farthest from the anionic impurities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Q‐switching lasers based on WS 2 SAs also exhibit the excellent performance. [ 240–242 ] For instance, Wang et al. reported that Q‐switching pulsed laser with WS 2 SA had a pulse of 430 ns, a pulse energy of 5.4 µJ, and a repetition rate from 64 to 90 kHz operating at 1.9 µm.…”
Section: Applicationsmentioning
confidence: 99%
“…With the development of the laser technology, high‐performance fiber lasers and high‐quality ultrashort laser pulse become more reliable. Since 1990, the SA that made of various materials has been emerging, such as carbon nanotubes (CNTs), black phosphorus, SnS 2 , MoS 2 , and WS 2 . Over the past several years, the metal sulfide, such as PbS NP, has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%